Species richness of polydorid species (Polychaeta: Spionidae) in the English Channel (France) and on the Pacific Coast of Tohoku District (Japan) - Dauvin, Jean-Claude; Sato-Okoshi, Waka; Okoshi, Kenji; Abe, Hirokazu (CCSD, 2023)
International audience Successive polychaete inventories have reported polydorids in the English Channel and there are some reports describing polydorids from the Pacific coast of Tohoku District, Japan. Species Richness in both areas is compared and discussed. Moreover, in March 2018, French-Japanese collaboration led to the collection of polydorid species from the shells of feral and cultured oysters Crassostrea gigas（THUNBERG, 1793）along the western coast of Normandy, France. Some species were also extracted from coralline algae and other calcareous substrates. Eight species were recorded belonging to four genera: Boccardia, Boccardiella, Dipolydora and Polydora. The two species Polydora hoplura Claparède, 1868 and Dipolydora giardi（Mesnii, 1893）were previously known in Normandy, along with another member of the genus Dipolydora that has not been identified to the species level. Boccardia proboscidea Hartman, 1940, Boccardiella hamata（Webster, 1879）and Polydora websteri Hartman in Loosanoff & Engle, 1943 represent new records in Normandy, while both Boccardia pseudonatrix Day, 1961 and Polydora onagawaensis Teramoto, Sato-Okoshi, Abe, Nishitani, Endo, 2013 are new species for European waters. We point out that collaboration with polychaete specialists to study well-known seas such as the English Channel would allow us to discover new species, expanding the list of species actually present. This study also highlights the need to continue this partnership further identify which polychaete species infest English Channel oysters.